REFLECTIONS ON REALITY: A REPRESENTATION ANALYSIS OF ETHICAL DILEMMAS IN BLACK MIRROR’S “CROCODILE” - Rinjani, Hayomi Gendis (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
This article explores the ethical complexities surrounding memory-extracting technologies by analyzing the speculative narrative of Black Mirror’s episode